Integrating metabolomics and network pharmacology to reveal the mechanisms of Delphinium brunonianum extract against nonalcoholic steatohepatitis. (15th July 2022) - Zhang, Kaihui; Yuan, Yue; Dawa, Zeren; Liu, Fangle; Yao, Yufeng; Wang, Meiqi; Zhu, Chenchen; Lin, Chaozhan
Abstract: Ethnopharmacological relevance: Herba Delphinii Brunoniani, a Tibetan Material Medica, derived from the aerial parts of Delphinium brunonianum Royle, possesses efficacy of cooling blood to remove apthogentic heat, and dispelling wind to arrest itching, and has been used for the treatment for liver disease according to Tibetan Medicine Theories in Shel Gong Shel Phreng . However, the mechanisms of action remain unclear. Aim of the study: This work aimed to investigate the efficacy mechanism of Delphinium brunonianum extract (DBE) on nonalcoholic steatohepatitis (NASH), a kind of liver disease by integrating serum metabolomics and network pharmacology analysis. Materials and methods: In this study, NASH model mice were established by a high-fat diet. The indexes of lipid accumulation, insulin resistance, and inﬂammatory reaction were used to evaluate the efficacy of DBE. A combination of UHPLC-QTOF-MS based metabolomics and network pharmacology was established to illustrate the serum biomarkers of NASH mice and to demonstrate the anti-NASH mechanisms of DBE. Serum metabolomics demonstrated potential metabolites and the corresponding metabolic pathways in the efficacy of DBE. Network pharmacology screened the targets of DBE against NASH. Finally, the mechanisms of DBE against NASH were verified by in-vivo pharmacology. Results: Metabolomics revealed that DBE significantly regulated the abnormal levels of twenty-two metabolites, which involved the biosynthesis of unsaturated fatty acids and steroid hormone, linoleic acid metabolism, arachidonic acid metabolism, and alpha-Linolenic acid metabolism pathways. Network pharmacology showed that DBE exhibited anti-NASH effects through regulating the targets of PTGS2, PLA2, ALOX5, ALOX15, FASN, and CYP450. Finally, united pharmacological verification result, we found that the mechanisms of DBE against NASH may be related to the regulation of the unsaturated fatty acids biosynthesis and the arachidonic acid metabolism pathway. Conclusions: Integrating serum metabolomic and network analysis, we found that DBE might inhibit the pathological process of NASH by regulating the relative targets and the metabolic pathways, which may be a potential mechanism for the anti-NASH efficacy of DBE. This integrated strategy also provided a rational way for revealing the pharmacodynamic mechanisms of multi-components, multi-targets, and multi-pathways in Traditional Chinese Medicine (TCM). Graphical abstract: Image 1 Highlights: For the first time to dissect the mechanisms of DBE against NASH by integrating metabolomics and network pharmacology. Five metabolic pathways were enriched to be closely relating to DBE against NASH under metabolomics. The mechanism might be related to the regulation of the unsaturated fatty acids biosynthesis pathway and arachidonic acid metabolism pathway. This integrated strategy had provided a rational way for revealing the pharmacodynamic mechanisms in DBE.